Lithium Fluoride in Electrolyte for Stable and Safe Lithium‐Metal Batteries - Tan, Yi‐Hong; Lu, Gong‐Xun; Zheng, Jian‐Hui; Zhou, Fei; Chen, Mei; Ma, Tao; Lu, Lei‐Lei; Song, Yong‐Hui; Guan, Yong; Wang, Junxiong; Liang, Zheng; Xu, Wen‐Shan; et al. (Advanced materials (Weinheim), 2021)
Electrolyte engineering via fluorinated additives is promising to improve cycling stability and safety of high‐energy Li‐metal batteries. Here, an electrolyte is reported in a porous lithium fluoride (LiF) strategy to enable efficient carbonate electrolyte engineering for stable and safe Li‐metal batteries. Unlike traditionally engineered electrolytes, the prepared electrolyte in the porous LiF nanobox exhibits nonflammability and high electrochemical performance owing to strong interactions between the electrolyte solvent molecules and numerous exposed active LiF (111) crystal planes. Via cryogenic transmission electron microscopy and X‐ray photoelectron spectroscopy depth analysis, it is revealed that the electrolyte in active porous LiF nanobox involves the formation of a high‐fluorine‐content (>30%) solid electrolyte interphase layer, which enables very stable Li‐metal anode cycling over one thousand cycles under high current density (4 mA cm−2). More importantly, employing the porous LiF nanobox engineered electrolyte, a Li || LiNi0.8Co0.1Mn0.1O2 pouch cell is achieved with a specific energy of 380 Wh kg−1 for stable cycling over 80 cycles, representing the excellent performance of the Li‐metal pouch cell using practical carbonate electrolyte. This study provides a new electrolyte engineering strategy for stable and safe Li‐metal batteries. Electrolyte engineering via fluorinated additives is promising to improve the cycling stability and safety of high‐energy Li‐metal batteries. The electrolyte in an active porous LiF nanobox involves the formation of a high‐fluorine‐content (>30%) solid electrolyte interphase layer to achieve a ≈3.5 Ah Li || LiNi0.8Co0.1Mn0.1O2 pouch cell with a specific energy of 380 Wh kg−1 under a practical carbonate electrolyte.